En plats att minnas : om att involvera ungdomar i en skapandeprocess - Johnsen, Sabina (SLU/Landscape Architecture (until 121231), 2011)
This Master thesis is about how to involve young people in a creative process. The aim is to see what methods can be applied to make them reach the kind of knowledge they need to be able to contribute to the creation of a memorial place. Issues such as if a place that displays death has a right to exist in an urban environment or why young people should be involved in the creative process are brought up and discussed in this thesis. The memorial place that the young people contribute to is unique, in some sense, due to it not commemorating any special event or person. The purpose of the memorial is rather to serve the public when larger catastrophes occur or to serve individuals who do not have a grave they can visit to commemorate their loved ones. The idea is to place the memorial in an urban setting in the city of Borås. In this thesis the process that the young people participate in is reported in a form similar to a diary where the reader can follow the developments of the young participants, from how they gain knowledge to how they develop their ideas. Their ideas and discussions are concretized in to two different suggestions which then are analyzed according to known theories concerning usage of space and place.